STRATIGRAPHIC AND TECTONIC EVOLUTION OF LA PURISIMA AREA (BAJA CALIFORNIA, MEXICO) DURING LATE OLIGOCENE AND MIOCENE: IMPLICATIONS FOR THE PACIFIC MARGIN EVOLUTION (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
The study of the Neogene sequences outcropping in the La Purisima area, Baja California Sur, Mexico, has demonstrated the presence of regional unconformities separating the main sedimentary bodies. On the basis of stratigraphic and structural analyses, we propose a new statigraphic framework in terms of depositional sequences. The Lower Sedimentary Sequence (San Gregorio Formation Auctorum) is mainly composed of silicized shales with phosphatic nodules and subordinate tuffìtes. The sequence is heavily deformed at several sites, and shows N-S trending folds, thrusts and normal faults. The Middle Sedimentary Sequence (Isidro Formation and lowermost Comondù Formation  Auctorum) consists of shallow marine fossiliferous sandstones with cineritic beds, capped by a thick fan of volcaniclastic sandstones. Small E-W trending thrusts and folds are associated to huge NNW-SSE and NW-SE open folds. The Upper Sedimentary Sequence is made of sub- horizontal sandstones and conglomerates probably representing the distal facies of the enormous alluvial fans of the Comondù Formation. Coquinoid limestones associated with volcaniclastic sandstones and conglomerates have been observed in between the lower and middle sequences, and are supposed to constitute a further allostratigraphic unit. The combined analysis of the stratigraphic and tectonic evidences is consistent with complex active wrenching along the Pacific margin.
Keywords: Stratigraphy; Paleontology; Wrench tectonics; Oligo-Miocene; Baja California Sur.